Phosphorylation of Golgi Peripheral Membrane Protein Grasp65 Is an Integral Step in the Formation of the Human Cytomegalovirus Cytoplasmic Assembly Compartment - G. Michael Rebmann; Robert Grabski; Veronica Sanchez; William J. Britt (mBio, 2016)
ABSTRACT Human cytomegalovirus (HCMV) is the largest member of the Herpesviridae and represents a significant cause of disease. During virus replication, HCMV alters cellular functions to facilitate its replication, including significant reorganization of the secretory and endocytic pathways of the infected cell. A defining morphologic change of the infected cell is the formation of a membranous structure in the cytoplasm that is designated the virion assembly compartment (AC), which consists of virion structural proteins surrounded by cellular membranes. The loss of normal Golgi compartment morphology and its relocalization from a juxtanuclear ribbonlike structure to a series of concentric rings on the periphery of the AC represents a readily recognized reorganization of cellular membranes in the HCMV-infected cell. Although trafficking of viral proteins to this compartment is required for the assembly of infectious virions, the functional significance of the reorganization of intracellular membranes like the Golgi membranes into the AC in the assembly of infectious virus remains understudied. In this study, we determined that Golgi membrane ribbon fragmentation increased during the early cytoplasmic phase of virion assembly and that Golgi membrane fragmentation in infected cells was dependent on the phosphorylation of an integral cis-Golgi protein, Grasp65. Inhibition of Golgi membrane fragmentation and of its reorganization into the AC resulted in decreased production of infectious particles and alteration of the incorporation of an essential protein into the envelope of the mature virion. These results demonstrated the complexity of the virus-host cell interactions required for efficient assembly of this large DNA virus. IMPORTANCE The human cytomegalovirus (HCMV)-induced reorganization of intracellular membranes that is required for the formation of the viral assembly compartment (AC) has been an area of study over the last 20 years. The significance of this virus-induced structure has been evinced by the results of several studies which showed that relocalization of viral proteins to the AC was required for efficient assembly of infectious virus. In this study, we have identified a mechanism for the fragmentation of the Golgi ribbon in the infected cell en route to AC morphogenesis. Identification of this fundamental process during HCMV replication allowed us to propose that the functional role of Golgi membrane reorganization during HCMV infection was the concentration of viral structural proteins and subviral structures into a single intracellular compartment in order to facilitate efficient protein-protein interactions and the virion protein trafficking required for the assembly of this large and structurally complex virus.